The Influence of Liquidity and Solvency on Bank Profitability: The Moderating Role of Dividend Policy - Nurhalizah, Sheila; Meythi, Meythi; Martusa, Riki (International Journal of Economics and Financial Issues, 2025)
The banking sector in Indonesia is facing significant challenges following the COVID-19 pandemic, including declining profitability, bankruptcy risks, and pressures on liquidity and solvency. The lack of research on the moderating role of dividend policy in the relationship between liquidity, solvency, and profitability is a major issue. This study aims to analyze the impact of liquidity (LDR) and solvency (CAR) on the profitability (ROA) of conventional banks listed on the Indonesia Stock Exchange (IDX) for the period 2014-2023, as well as to examine the role of dividend policy (DPR) as a moderating variable. Using a quantitative approach, secondary data from Refinitiv Eikon and financial reports of 22 banks with 175 observations will be analyzed through moderation regression analysis (MRA) using STATA. The results show that liquidity (LDR) has a negative and insignificant effect on ROA, while solvability (CAR) has a positive and significant effect. Dividend policy (DPR) does not moderate the relationship between liquidity or solvability and profitability. These findings emphasize the importance of capital adequacy for profitability, support signaling theory, but indicate the need for an evaluation of liquidity strategies. Dividend policy is not proven to be a moderating mechanism, suggesting that banks should prioritize capital management and regulators should consider contextual factors in dividend policy.